Simulation of the operation of a voltage inverter as part of an autonomous wind power plant with aerodynamic multiplication based on an asynchronous generator with a phase rotor - Strunkin, Hlib (Technologies and Engineering, 2025)
In the context of energy scarcity caused by the destruction of energy infrastructure, instability of electricity supply and growing demand for autonomous energy sources, there is a need to develop independent and efficient energy supply systems. Of particular importance are wind power plants that are able to function independently, ensuring the stability of power supply even in crisis conditions. In this regard, it is important to investigate promising solutions that meet modern quality standards and can integrate into autonomous energy systems. The purpose of the study was to confirm the efficiency of calculating inverter filters in static and dynamic modes, and under unbalanced load conditions. This was achieved on the basis of simulation modelling of an autonomous wind power plant with aerodynamic multiplication operating on the basis of an asynchronous generator with a phase rotor and excitation from a voltage inverter. A simulation model of an autonomous wind power plant and inverter parameters calculated according to the author’s methods in the PSIM environment were described. A Fourier analysis of the harmonic composition of the output voltage of the inverter was performed programmatically, and its harmonic coefficient, which did not exceed 5%, was calculated in accordance with the current standard. It was proved that the excitation from the voltage inverter improves its operation under unbalanced load and release and surge. The results of modelling the output voltage of the inverter were compared with the requirements of standards for continuous power sources. Based on the results of simulation modelling of an autonomous wind power plant with aerodynamic multiplication, the efficiency of calculating voltage inverter filters for an asynchronous generator with a phase rotor was confirmed. The methods have shown their effectiveness both in static and dynamic modes, and under conditions of unbalanced load.